Ab initio X‐ray structural characterization of an inclusion compound with a compositionally disordered chiral guest: no prior knowledge of the crystal composition. Issue 3 (9th February 2016) - Guzei, Ilia A.; Miles, Kelsey C.
Abstract : The entire crystal structure of a host/guest/impurity clathrate compound was solved ab initio with an intrinsic phasing program and substantiated by other analytical techniques. The host is ordered, whereas the guest molecule is compositionally disordered (85:15) with its hydroperoxy autoxidation product. Abstract : The crystal structure and absolute configuration of a molecular host/guest/impurity inclusion complex were established unequivocally in spite of our having no prior knowledge of its chemical composition. The host (4 R, 5 R )‐4, 5‐bis(hydroxydiphenylmethyl)‐2, 2‐dimethyl‐1, 3‐dioxolane, (I), displays expected conformational features. The crystal‐disordered chiral guest 4, 4a, 5, 6, 7, 8‐hexahydronaphthalen‐2(3 H )‐one, (II), is present in the crystal 85.1 (4)% of the time. It shares a common site with 4a‐hydroperoxymethyl‐4, 4a, 5, 6, 7, 8‐hexahydronaphthalen‐2(3 H )‐one, (III), present 14.9 (4)% of the time, which is the product of autoxidation of (II). This minor peroxide impurity was isolated, and the results of nuclear magnetic resonance, mass spectrometry, and X‐ray fluorescence studies are consistent with the proposed structure of (III). The complete structure was therefore determined to be (4 R, 5 R )‐4, 5‐bis(hydroxydiphenylmethyl)‐2, 2‐dimethyl‐1, 3‐dioxolane–4, 4a, 5, 6, 7, 8‐hexahydronaphthalen‐2(3 H )‐one–4a‐hydroperoxymethyl‐4, 4a, 5, 6, 7, 8‐hexahydronaphthalen‐2(3 H )‐one (1/0.85/0.15), C31 H30 O4 ·0.85C10 H14 O·0.15C10 H14 O3, (IV). There are host–host, host–guest, and host–impurity hydrogen‐bonding interactions of types S and D in the solid state. We believe that the crystals of (IV) were originally prepared to establish the chirality of the guest (II) by means of X‐ray diffraction analysis of host/guest crystals obtained in the course of chiral resolution during cocrystallization of (II) with (I). In spite of the absence of `heavy' elements, the absolute configurations of all anomeric centres in the structure are assigned as R based on resonant scattering effects.